2019
DOI: 10.1152/ajpregu.00309.2018
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of a lifestyle intervention program on C-reactive protein: impact of cardiorespiratory fitness in obese adolescents with sleep disturbances

Abstract: The objectives of this study were to assess the relationship between inflammation and obstructive sleep apnea (OSA) and determine whether the lifestyle program’s effects on inflammatory markers are associated with changes in anthropometric parameters, cardiorespiratory fitness, sleep duration, and OSA severity in severely obese adolescents. Participants were aged 14.6 (SD 1.2) yr, with a body mass index (BMI) of 40.2 (SD 6.5) kg/m2. Sleep, anthropometric parameters, glucose metabolism, inflammatory profile, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Quasi-experimental lifestyle intervention studies have demonstrated significant increases in adiponectin [32][33][34]71,72], reductions in IL-6 [73], no changes in IL-10 [74,75], and conflicting results on TNF-α [62,74,75]. Two RCTs failed to support treatment effects on total adiponectin in response to lifestyle intervention compared to control groups, despite significant reductions in weight, adiposity, and C-reactive protein (established marker of systemic inflammation) and increases in insulin sensitivity [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Quasi-experimental lifestyle intervention studies have demonstrated significant increases in adiponectin [32][33][34]71,72], reductions in IL-6 [73], no changes in IL-10 [74,75], and conflicting results on TNF-α [62,74,75]. Two RCTs failed to support treatment effects on total adiponectin in response to lifestyle intervention compared to control groups, despite significant reductions in weight, adiposity, and C-reactive protein (established marker of systemic inflammation) and increases in insulin sensitivity [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of paediatric overweight and obesity remains alarming worldwide (15) , accompanied by early metabolic (24) , sleep (25,26) and functional (27) impairments, amongst others, calling for effective preventive and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The present work also certainly lacks the evaluation of some physiological factors that are implicated in the control of appetite. Indeed, it would have been interesting to also evaluate the evolution of the ghrelin and leptin levels, for instance, particularly since their respectively increase [ 28 ] and decrease [ 29 ] in response to similar weight loss interventions in adolescents with obesity could partly explain our results.…”
Section: Discussionmentioning
confidence: 99%